2022
DOI: 10.1136/rapm-2021-103427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of suprainguinal fascia iliaca compartment block on postoperative opioid consumption and functional recovery in posterolateral-approached total hip arthroplasty: a single-blind randomized controlled trial

Abstract: IntroductionPosterolateral-approached total hip arthroplasty (PLTHA) is followed by moderate to severe postoperative pain. Suprainguinal fascia iliaca compartment block (SFICB) has been proposed as a promising analgesia technique.MethodsData from 86 patients scheduled for PLTHA with spinal anesthesia were analyzed in this prospective randomized controlled trial. Patients were randomly divided into two groups of 43 patients each. As opposed to the control group (group C), ropivacaine group (group R) received ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In a single-blind randomized controlled trial including 86 patients who underwent posterolateral approach total hip arthroplasty, Carella et al 1 assessed the effects of suprainguinal fascia iliaca compartment block on postoperative opioid consumption and functional recovery and showed that the suprainguinal fascia iliaca compartment block provided opioid sparing, improved postoperative pain control and enhanced functional recovery. Other than the limitations described by authors in the discussion, however, this study used a single-mode postoperative analgesia strategy in the control patients, that is, patient-controlled analgesia with morphine.…”
mentioning
confidence: 99%
“…In a single-blind randomized controlled trial including 86 patients who underwent posterolateral approach total hip arthroplasty, Carella et al 1 assessed the effects of suprainguinal fascia iliaca compartment block on postoperative opioid consumption and functional recovery and showed that the suprainguinal fascia iliaca compartment block provided opioid sparing, improved postoperative pain control and enhanced functional recovery. Other than the limitations described by authors in the discussion, however, this study used a single-mode postoperative analgesia strategy in the control patients, that is, patient-controlled analgesia with morphine.…”
mentioning
confidence: 99%
“…The fascia iliaca block (FIB) is an established and effective technique, especially when ultrasound (US) guidance and proximal approaches are used. Recent studies have recently demonstrated that US guided FIB with a supra-inguinal approach is associated with improved pain control and significant opioid-sparing effect after THA [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…A longitudinal supra-inguinal approach to the fascia iliaca compartment has been shown to be efficient at relieving pain after both the anterior and posterolateral approach for THA 9,10 . The supra-inguinal fascia iliaca block (SFIB) performed in patients having received spinal anaesthesia for surgery reduces postoperative opioid consumption, improves postoperative pain management and functional performance during the first 48 h after surgery 10 . Similarly, the pericapsular nerve group (PENG) block has been demonstrated to be effective in PLTHAs, not only regarding postoperative pain management but also because of preservation of quadriceps femoris strength 11–13 .…”
Section: Introductionmentioning
confidence: 99%